Metal / ceramic bonded body and method for manufacturing metal / ceramic bonded body

By using welding materials containing Ag, Cu and active metal elements, the first layer with the active metal compound phase and the second layer with the titanium nitride phase are formed, and the problems of bonding strength and thermal cycle reliability of the existing metal cermet bonding methods are solved under high temperature pressure, and efficient bonding performance and stable thermal cycle performance are achieved.

JP2025058601APending Publication Date: 2025-04-09PROTERIAL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023168636
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The existing metal cermet bonding methods are prone to joint strength and thermal cycle reliability under high temperature pressure, especially when the thermal expansion coefficient of the ceramic material is different from that of the metal material, and problems of stress concentration and joint strength are prone to decrease.

Method used

The bonding strength and thermal cycle reliability of the metal cermet bonding are used to form a first layer with an active metal compound phase and a second layer with a titanium nitride-containing phase, so as to improve the bonding strength and thermal cycle reliability of the metal cermet bonding.

Benefits of technology

The bonding strength and thermal cycle reliability of metal cermet bonding are significantly improved, and efficient bonding performance can be maintained under high temperature and high pressure conditions, avoiding the problems of stress concentration and joint strength reduction caused by differences in thermal expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058601000001_ABST
    Figure 2025058601000001_ABST
Patent Text Reader

Abstract

To provide a metal / ceramic bonded body having high bonding strength and high thermal cycle reliability.SOLUTION: A metal / ceramic bonded body comprises: a metal member; a ceramic member bonded to the metal member; and a bonding layer formed on a bonding surface between the metal member and the ceramic member, containing Ag and Cu, and further containing at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er. The bonding layer comprises: a first layer constituting an interface with the metal member and containing an Ag phase consisting mainly of Ag and a Cu phase consisting mainly of Cu; and a second layer constituting an interface with the ceramic member and containing a compound of the active metal element and in contact with the first layer. An active metal compound phase containing a compound of the active metal element is present in the first layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a metal / ceramic bonded body and a method for producing a metal / ceramic bonded body. [Background technology]

[0002] There is a growing demand for a joint made by joining a metal member and a ceramic member (metal / ceramic joint) as an insulating circuit board for power electronics semiconductor devices such as inverters and converters, and the current density and size are becoming higher. This causes higher thermal stress, and there is a need for circuit boards with long life and high strength, and ultimately for high-strength joints between metals and ceramics.

[0003] For bonding metals and ceramics, particularly insulated circuit boards used in semiconductor devices, a bonding method that uses a eutectic of copper (Cu) and copper oxide (CuO) called Direct Copper Bonding (DCB) to directly heat bond Cu to oxide ceramics, and a bonding method that uses an active metal brazing material called Active Metal Brazing (AMB) are used.

[0004] Among these, the AMB method has been attracting attention as a joining method that can obtain high joining strength, and a Ag-Cu-Ti based brazing material is used as a typical joining material. For example, in Patent Document 1, after placing an Ag-Cu-Sn-Ti based brazing material on a ceramic substrate, Cu is laminated and a 1.0×10 -3 A metal / ceramic bond is obtained by heat treatment at 780°C to 850°C in a vacuum of 100 Pa or less.

[0005] There are also cases where brazing filler metal compositions that do not contain Ag have been investigated, and for example, Patent Document 2 proposes a ceramic circuit board in which a copper plate and a ceramic substrate are bonded together using a Cu-Mg-Ti brazing filler metal. According to Patent Document 2, a metal / ceramic bonded body can be obtained by laminating a Cu plate and a ceramic substrate together via an active metal foil and a magnesium (Mg) foil, and then subjecting the laminate to a heat treatment within a range of 700°C to 830°C. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6743073 [Patent Document 2] International Publication No. 2021 / 033421 Summary of the Invention [Problem to be solved by the invention]

[0007] At the interface between metal and ceramics using a joining method using an active metal brazing material, the active metal reacts with the ceramics to form an interface reaction layer, which can provide a joined body with a certain degree of high joining strength and reliability. However, because the metal member and the ceramic member have significantly different thermal expansion coefficients, strain and defects may increase in the joining layer disposed between the metal member and the ceramic member, which may lead to a decrease in joining strength and reliability.

[0008] When Cu and aluminum nitride (AlN) or silicon nitride (Si3N4) are joined via an Ag-Cu-Sn-Ti brazing material as in Patent Document 1, the thermal expansion coefficient of Si3N4 is lower than that of the joining layer disposed between Cu and Si3N4, which may cause problems with reliability in thermal cycle tests (hereinafter referred to as thermal cycle reliability).

[0009] Also, as in Patent Document 2, the thermal stress caused by the difference in thermal expansion coefficient between the copper member and the ceramic member can be alleviated by dispersing an active metal oxide phase with a low thermal expansion coefficient in the bonding layer. However, a magnesium oxide (MgO) layer that is prone to brittle fracture is formed in a layered shape between the copper member and the ceramic member, which may reduce the bonding strength.

[0010] An object of the present disclosure is to provide a metal / ceramic bonded body having high bonding strength and high thermal cycle reliability. [Means for solving the problem]

[0011] According to one aspect of the present disclosure, A metal member; a ceramic member joined to the metal member; a bonding layer formed on a bonding surface between the metal member and the ceramic member, the bonding layer containing Ag and Cu and further containing at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er; The bonding layer is A first layer that forms an interface with the metal member and includes an Ag phase mainly composed of Ag and a Cu phase mainly composed of Cu; a second layer that forms an interface with the ceramic member, contains a compound of the active metal element, and is in contact with the first layer; A metal / ceramic joint is provided in which an active metal compound phase containing a compound of the active metal element is present in the first layer.

[0012] According to another aspect of the present disclosure, A step of arranging a metal member and a ceramic member so as to be laminated with a brazing material interposed therebetween; and heating and holding the laminate of the metal member and the ceramic member while applying pressure in a lamination direction, The brazing material contains 50 to 80 at % Ag, 10 to 40 at % Cu, and a total of 0.1 to 10 at % of at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er, and the Ag and Cu are contained in a state where the average particle size is 45 μm or less. The method for producing a metal / ceramic bonded body includes a step of holding at a predetermined first temperature and a step of holding at a temperature higher than the first temperature, and at the end of the step of holding at the first temperature, the carbon content in the brazing material is 0.1 mass% or more and 10 mass% or less. Effect of the Invention

[0013] According to the present disclosure, it is possible to provide a metal / ceramic bonded body having high bonding strength and high thermal cycle reliability. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a partial cross-sectional schematic diagram of a metal / ceramic bonded body 100 according to one embodiment of the present disclosure. [Diagram 2] 2(a) and 2(b) are cross-sectional photographs (SEM images) of the first layer 31 and its surroundings. [Diagram 3] FIG. 3 is an enlarged photograph (STEM image) of the active metal compound phase 33. [Figure 4] FIG. 4 shows an electron energy loss (EELS) spectrum of the active metal compound phase 33 analyzed by a scanning transmission electron microscope. [Diagram 5] FIG. 5( a ) is a diagram showing a schematic diagram of shear stress applied to the bonding layer 30 , and FIG. 5( b ) is a diagram showing a schematic diagram of tensile stress applied to the bonding layer 30 . [Figure 6]FIG. 6(a) shows a state in which a metal member 10 and a ceramic member 20 are arranged with a brazing material 50 interposed therebetween, FIG. 6(b) shows a state in which a laminate of the metal member 10 and the ceramic member 20 is heated while being pressurized, and FIG. 6(c) shows a manufactured metal / ceramic bonded body 100. [Figure 7] FIG. 7 is a schematic diagram showing a state in which a shear strength test is carried out. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <One aspect of the present disclosure> Hereinafter, one embodiment of the present disclosure will be described with reference to the above-mentioned drawings. Note that all drawings used in the following description are schematic. The dimensions and ratios of each element shown in the drawings do not necessarily match those in reality. Furthermore, the dimensions and ratios of each element do not necessarily match between drawings. Note that in this specification, "A to B" means a numerical range of "A or more and B or less."

[0016] (1) Structure of metal / ceramic joint As shown in FIG. 1, a metal / ceramic bonded body 100 includes a metal member 10, a ceramic member 20 bonded to the metal member 10, and a bonding layer 30 formed on the bonding surface between the metal member 10 and the ceramic member 20.

[0017] The metal member 10 is made of, for example, pure copper, a copper alloy, pure nickel, a nickel alloy, or the like. For example, oxygen-free copper, tough pitch copper, and phosphorus-deoxidized copper can be used as the pure copper. For example, an alloy containing copper (Cu) as a main element and at least one element selected from the group consisting of zinc (Zn), tin (Sn), phosphorus (P), aluminum (Al), beryllium (Be), cobalt (Co), nickel (Ni), iron (Fe), and manganese (Mn) can be used as the copper alloy. There is no particular limitation on the shape and dimensions of the metal member 10, but when the metal / ceramic bonded body 100 is used as a constituent material of an insulating circuit board, it can be, for example, a flat plate having a thickness in the range of 0.1 mm to 4.0 mm. In this embodiment, the case where the metal member 10 is made of pure copper will be described.

[0018] The ceramic member 20 is made of, for example, silicon nitride (Si3N4), aluminum nitride (AlN), silicon carbide (SiC), aluminum oxide (Al2O3), diamond, or the like. There are no particular limitations on the shape or dimensions of the ceramic member 20, but when the metal / ceramic bonded body 100 is used as a constituent material of an insulating circuit board, it may be, for example, a flat plate having a thickness in the range of 0.2 mm to 4.0 mm. In this embodiment, a case where the ceramic member 20 is made of silicon nitride (Si3N4) will be described.

[0019] A bonding layer 30 is formed between the metal member 10 and the ceramic member 20 along the bonding surfaces 10s and 20s. The bonding layer 30 contains silver (Ag) and copper (Cu), and further contains at least one active metal element selected from the group consisting of titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), magnesium (Mg), calcium (Ca), yttrium (Y), cerium (Ce), lanthanum (La), samarium (Sm), ytterbium (Yb), neodymium (Nd), gadolinium (Gd), erbium (Er), and the like. When the ceramic member 20 is Si3N4 or AlN, it is preferable to use Ti, V, Nb, Cr, Mo, Ca, or Mg as the active metal element. In this embodiment, the case where Ti is used as the active metal element will be described.

[0020] As described later, the bonding layer 30 is formed by the brazing material 50 containing Ag, Cu, and the above-mentioned active metal elements in a predetermined ratio, reacting with the metal member 10 and the ceramic member 20. The brazing material 50 used in this embodiment is an Ag-Cu brazing material, and contains, for example, 50 to 80 at% Ag, 10 to 40 at% Cu, and a total of 0.1 to 10 at% active metal element (Ti in this embodiment). The brazing material 50 may further contain, for example, 0.1 to 30 at% of any one element selected from tin (Sn), indium (In), and zinc (Zn). In other words, the brazing material 50 used in this embodiment contains 10 to 40 at% Cu, 0.1 to 10 at% total active metal elements, and the balance (excluding inevitable impurities) is Ag, or contains 10 to 40 at% Cu, 0.1 to 10 at% total active metal elements, and 0.1 to 30 at% of any one element selected from tin (Sn), indium (In), and zinc (Zn), and the balance (excluding inevitable impurities) is Ag. By using such a brazing material 50 and performing bonding by the method described below, the bonding layer 30 in this embodiment exhibits various characteristics described below.

[0021] 1, the bonding layer 30 has a laminated structure of a first layer 31 that constitutes an interface with the metal member 10, and a second layer 32 that constitutes an interface with the ceramic member 20 and is in contact with the first layer 31. The thickness of the first layer 31 is, for example, 1 to 2000 μm, and the thickness of the second layer 32 is, for example, 1 to 2000 nm.

[0022] 2(a) and 2(b) are cross-sectional photographs (SEM images) of the first layer 31 and its surroundings. As shown in Fig. 2(a) and 2(b), the first layer 31 has an Ag phase 31A (light gray part in the figure) and a Cu phase 31B (dark gray part in the figure).

[0023] The Ag phase 31A is mainly composed of Ag (e.g., 90 at % or more of Ag). The Cu phase 31B is mainly composed of Cu (e.g., 90 at % or more of Cu). The Ag phase 31A and the Cu phase 31B may contain active metal elements such as Ti contained in the brazing material 50, or Si, Al, etc. contained in the ceramic member 20.

[0024] As shown in FIG. 2(a) and FIG. 2(b), the first layer 31 has an active metal compound phase 33 (for example, the outer peripheral portion of the region indicated by the radius R in FIG. 2(a)) containing a compound of an active metal element (hereinafter, also referred to as an active metal compound). As shown in FIG. 2(a) and FIG. 2(b), the active metal compound phase 33 is preferably present so as to extend in a curved shape without forming a large mass. The presence of the active metal compound phase 33 in the first layer 31 can mitigate the generation of thermal stress caused by the difference in thermal expansion coefficient between the metal member 10 and the ceramic member 20, and can improve the bonding strength and thermal cycle reliability. When the active metal element is Ti, examples of the compound of the active metal element include Ti-C, Ti-N, Ti-O, Ti-(C,N), Ti-(N,O), Ti-(C,O), Ti-Si, and the like. Note that the active metal compound phase 33 is not shown in FIG. 1.

[0025] As shown in FIG. 2(a) and FIG. 2(b), the active metal compound phase 33 is preferably present so as to surround at least one of the Ag phase 31A and the Cu phase 31B (shell-shaped). The presence of the active metal compound phase 33 in such a manner can alleviate the generation of thermal stress between the Ag phase 31A and the Cu phase 31B, and can further improve the bonding strength and thermal cycle reliability. The active metal compound phase 33 being present so as to surround the Ag phase 31A or the Cu phase 31B includes the case where the active metal compound phase 33 forms a closed space (closed curve in a cross-sectional photograph) and completely surrounds a certain region, as well as the case where the active metal compound phase 33 is not present in a part of the periphery of the region. In this specification, for example, when the active metal compound phase 33 covers 80% or more of the surface area of ​​the region (the periphery in a cross-sectional photograph), the active metal compound phase 33 is expressed as being present so as to surround the region.

[0026] In the active metal compound phase 33, at least one of a carbide of an active metal element (e.g., TiC), a nitride of an active metal element (e.g., TiN), and an oxide of an active metal element (e.g., α-TiO, Ti3O, Ti2O, β-TiO, γ-TiO, β-Ti2O3, TiO2) is preferably present. In addition, in the active metal compound phase 33, two (or three) of a carbide of an active metal element, a nitride of an active metal element, and an oxide of an active metal element may be present (coexist). When the active metal compound phase 33 is present in such a manner, it becomes easier to alleviate the generation of thermal stress between the Ag phase 31A and the Cu phase 31B, and it is possible to further improve the bonding strength and the thermal cycle reliability.

[0027] The diameter R of the region surrounded by the active metal compound phase 33 is preferably, for example, 1 μm or more and 20 μm or less. This can further improve the bonding strength and thermal cycle reliability. The diameter R may be the circle-equivalent diameter of the region surrounded by the active metal compound phase 33 in the cross-sectional photographs shown in Figures 2(a) and 2(b).

[0028] Fig. 3 is an enlarged photograph (STEM image) of the active metal compound phase 33. As shown in Fig. 3, the active metal compound phase 33 is preferably formed by a large number of active metal compound particles connected together. The thickness d of the active metal compound phase 33 is preferably, for example, 10 nm or more and 1 µm or less. In addition, the particle size of the active metal compound particles in the active metal compound phase 33 is preferably, for example, 10 nm or more and 30 nm or less. This can further improve the bonding strength and thermal cycle reliability.

[0029] The active metal compound phase 33 may be present non-uniformly in the first layer 31. For example, 2 When the area ratio of the active metal compound phase 33 in the region is measured multiple times (for example, three times) in different observation fields, the difference between the maximum value and the minimum value of the area ratio of the active metal compound phase 33 may be 10% or more. In particular, as shown in FIG. 2(b), it is preferable that the active metal compound phase 33 is uniform in the thickness direction of the first layer 31 and non-uniform (having density variations) in the creeping direction (the direction of the bonding surfaces 10s and 20s). The presence of the active metal compound phase 33 in such a form can further improve the bonding strength and thermal cycle reliability. When measuring the area ratio of the active metal compound phase 33 in the cross section of the first layer 31, for example, it may be calculated by image analysis of a cross-sectional photograph as shown in FIG. 2(a) and FIG. 2(b), or the area of ​​the active metal compound phase 33 may be calculated by the product of the total value of the circle equivalent diameter R of each region surrounded by the active metal compound phase 33 and the average thickness d of the active metal compound phase 33.

[0030] In the cross section of the first layer 31 (for example, a cross section of 500 μm 2 In the region (a), the area ratio of the active metal compound phase 33 is preferably, for example, 15% or less. If the area ratio of the active metal compound phase 33 exceeds 15%, the effect of improving thermal cycle reliability may decrease. In contrast, by setting the area ratio of the active metal compound phase 33 to 15% or less, it is possible to sufficiently improve reliability in a thermal cycle test.

[0031] Fig. 4 is an example of an electron energy loss (EELS) spectrum obtained by analyzing the active metal compound phase 33 with a scanning transmission electron microscope. As shown in Fig. 4, when the active metal compound phase 33 is subjected to an EELS analysis, it can be confirmed that the spectrum has two peaks (indicated by arrows in the figure) derived from Ti in the form of an active metal compound in the range of 450 to 470 eV.

[0032] Of the bonding layer 30, the second layer 32 constituting the interface with the ceramic member 20 is mainly composed of titanium nitride (TiN) (e.g., 50 at% or more of TiN), which is a nitride of an active metal element (Ti in this embodiment). When the ceramic member 20 is made of silicon nitride, the second layer 32 may contain a compound represented by the composition formula Ti5Si3. The active metal compound (e.g., TiN) in the second layer 32 exists, for example, in a layer shape along the interface with the ceramic member 20.

[0033] In this embodiment, the second layer 32 may further include a silicide or aluminide of an active metal element. When the ceramic member 20 is made of Si3N4, the second layer 32 may include a silicide of an active metal element such as Ti5Si3, and when the ceramic member 20 is made of AlN, the second layer 32 may include an aluminide of an active metal element such as TiAl. Hereinafter, as an example, a case where the second layer 32 includes Ti5Si3 will be described. The silicide or aluminide of an active metal element such as Ti5Si3 may be present in a region of the second layer 32 from the interface with the first layer 31 to 60% of the thickness Tx of the second layer 32, for example.

[0034] By virtue of these various features, this embodiment succeeds in significantly increasing the bonding strength between the metal member 10 and the ceramic member 20 and the thermal cycle reliability.

[0035] Specifically, the shear strength of the bonding layer 30 in this embodiment is 10 MPa or more, preferably 50 MPa or more, and the tensile strength of the bonding layer 30 in this embodiment is 17.3 MPa or more, preferably 86.6 MPa or more.

[0036] The shear strength of the bonding layer 30 here means the magnitude of shear stress per unit area required to break (shear fracture) the bonding layer 30 when stress (shear stress) is applied to the bonding layer 30 so as to displace the metal member 10 and the ceramic member 20 in opposite directions along a direction parallel to the bonding surfaces 10s and 20s, as shown in Fig. 5(a). The tensile strength of the bonding layer 30 means the magnitude of tensile stress per unit area required to break (peeling fracture) the bonding layer 30 when stress (tensile stress) is applied to the bonding layer 30 so as to pull the metal member 10 and the ceramic member 20 away from each other along a direction perpendicular to the bonding surfaces 10s and 20s, as shown in Fig. 5(b).

[0037] The metal / ceramic bonded body 100 of this embodiment also has high thermal cycle reliability. Specifically, for example, when a thermal cycle of -50°C for 30 minutes and 150°C for 30 minutes is performed 200 times, no cracks in the ceramic member 20 and no peeling of the metal member 10 are observed, which is high thermal cycle reliability. The presence or absence of cracks in the ceramic member 20 and peeling of the metal member 10 can be confirmed by, for example, ultrasonic testing (SAT).

[0038] (2) Manufacturing method of metal / ceramic bonded body Next, a method for producing the above-mentioned metal / ceramic bonded body 100 will be described with reference to FIGS. 6(a) to 6(c).

[0039] First, as shown in FIG. 6(a), the above-mentioned metal member 10 and the above-mentioned ceramic member 20 are arranged so as to be laminated with the brazing material 50 interposed therebetween.

[0040] As described above, for example, a material containing 50 to 80 at% Ag, 10 to 40 at% Cu, and a total of 0.1 to 10 at% of the above-mentioned active metal element (Ti in this embodiment) can be used as the brazing material 50. The brazing material 50 may further contain, for example, 0.1 to 30 at% of any one element selected from tin (Sn), indium (In), and zinc (Zn).

[0041] The Ag and Cu contained in the brazing material 50, when used in combination with the active metal element, improve the wettability with the ceramic member 20. In addition, the brazing material 50 acts to impart the various characteristics described above to the bonding layer 30 formed by the reaction of the brazing material 50 with the metal member 10 and the ceramic member 20. In addition, the active metal element contained in the brazing material 50 reacts with the ceramic member 20 to form the second layer 32, and acts to increase the bonding strength between the bonding layer 30 and the ceramic member 20.

[0042] In the brazing material 50, Ag can be contained in the form of a simple substance (pure Ag) or an intermetallic compound with another metal element. Cu can be contained in at least one of the following forms: simple substance (pure Cu), hydride (CuH), and an intermetallic compound with an active metal element (e.g., a Cu-Ti compound). For example, when Ti is selected as the active metal element, it can be contained in at least one of the following forms: simple substance (pure Ti), hydride (TiH2), an intermetallic compound with Ag, and an intermetallic compound with Cu.

[0043] In the brazing material 50, Ag and Cu must be contained in a state in which the particle size is small (for example, the average particle size (D50) is 45 μm or less) either as a single element or as an alloy containing Ag and Cu. This allows the active metal compound phase 33 to be formed as shown in FIG. 2(a) and FIG. 2(b). The lower limit of the average particle size of Ag and Cu is not particularly limited, but is, for example, 5 μm or more. In addition, it is preferable that Ti is also contained in the brazing material 50 in a state in which the particle size is small (for example, the average particle size (D50) is 45 μm or less). This makes it easier to form the active metal compound phase 33.

[0044] The brazing material 50 may be in the form of a powder, a foil, or a paste. From the viewpoint of facilitating the formation of the active metal compound phase 33 as shown in Fig. 2(a) and Fig. 2(b), the brazing material 50 is preferably in the form of a powder or a paste. When the brazing material 50 is in the form of a paste, the main solvent may be an alcohol such as terpineol or butanediol or a toluene, the binder may be polyvinyl alcohol, ethyl cellulose, polymethacrylic acid, polyacrylic, or the like, and the surfactant may be a cationic, anionic, or nonionic activator. The brazing material 50 may further contain a plasticizer or a dispersant.

[0045] The brazing material 50 can be disposed on the intended joining surfaces 10s', 20s' of the metal member 10 and the ceramic member 20 by any known method such as screen printing, transfer, dispensing, inkjet, spray coating, sputtering, or vapor deposition.

[0046] Next, as shown in FIG. 6(b), the laminate 100' of the metal member 10 and the ceramic member 20 arranged via the brazing material 50 is heated and held in a predetermined atmosphere while being pressurized in the lamination direction. The predetermined atmosphere may be any one of a vacuum atmosphere (reduced pressure atmosphere), an inert gas atmosphere, and a reducing atmosphere. In this embodiment, the bonding is performed in an N2 atmosphere, so that the active metal compound phase 33 containing TiN and the like is easily formed in the first layer 31. In addition, the bonding in an N2 atmosphere has a higher oxygen concentration than a vacuum atmosphere, so that the active metal compound phase 33 containing TiO and the like is also easily formed in the first layer 31. The inert gas atmosphere may contain a small amount (for example, about 5% or less) of gas other than the inert gas, such as H2 gas.

[0047] Here, for example, since the brazing paste contains carbon derived from organic components, it has generally been considered preferable to perform a process of removing carbon (degreasing process) before bonding. In contrast, in this embodiment, bonding is performed while leaving 0.1 mass% to 10 mass% of carbon in the brazing material 50, so that the active metal compound phase 33 containing TiC and the like is easily formed in the first layer 31. Specifically, a process of holding at a predetermined first temperature (carbon amount adjustment process) is performed before bonding, and the carbon amount in the brazing material 50 is set to 0.1 mass% to 10 mass% at the end of the carbon amount adjustment process, so that the active metal compound phase 33 containing TiC and the like is easily formed in the first layer 31. The first temperature may be a temperature lower than the melting point of the brazing material 50, and is preferably 50% to 90% of the melting point (absolute temperature) of the brazing material 50. This can mitigate the generation of thermal stress caused by the difference in thermal expansion coefficient between the metal member 10 and the ceramic member 20, and improve the bonding strength and thermal cycle reliability. The carbon content adjustment step can be carried out, for example, by placing the laminate 100' in a heating furnace, introducing an inert gas or the like into the heating furnace, and heating while exhausting the gas in the furnace.

[0048] After the carbon content adjustment process, the temperature is held higher than the first temperature to perform bonding. The heating temperature during bonding may be, for example, equal to or higher than the melting point of the brazing material 50 and equal to or lower than the melting point of the metal member 10. The heating temperature is preferably equal to or lower than 115% of the melting point (absolute temperature) of the brazing material 50, and more preferably equal to or higher than 101% and equal to or lower than 110% of the melting point (absolute temperature) of the brazing material 50. This improves the diffusibility of the active metal element, making it easier to form the second layer 32. When using the brazing material 50 for this embodiment, the heating temperature is preferably, for example, equal to or higher than 735°C and equal to or lower than 900°C. As the heat treatment furnace used for bonding, a known furnace such as a stationary batch furnace, a multi-chamber furnace, or a belt conveyor furnace can be used.

[0049] Other conditions for bonding are exemplified as follows. Oxygen concentration: 0.01 ppm or more and 1000 ppm or less Pressure: 0.5kPa or more Holding time: No particular limit, but for example, 3 minutes or more and 120 minutes or less

[0050] During heating, it is necessary that a liquid phase is formed in a part of the brazing material 50, and in addition, the active metal element is required to be melted in the liquid phase. This state can be created by setting the heating temperature at 735°C or higher. However, if the heating temperature is too high, it may be difficult to form a liquid phase, or voids may occur in the bonding layer 30 to be formed. By setting the heating temperature at 900°C or lower, it is possible to avoid such problems. By setting the pressure at 0.5 kPa or higher, it is possible to maintain the adhesive state between the metal member 10 and the ceramic member 20 via the brazing material 50, and it is possible to increase the bonding strength between the metal member 10 and the ceramic member 20. There is no particular limit to the upper limit of the pressure, but it can be set to about 20 kPa, for example.

[0051] Thereafter, the heated laminate 100' is cooled, resulting in the production of a metal / ceramic bonded body 100 having the various characteristics described above, as shown in FIG.

[0052] When the metal / ceramic bonded body 100 is used as an insulating circuit board, etching may be performed after placing an etching resist on the metal member 10 in order to form a circuit pattern on the metal member 10. The type of etching resist is not particularly limited, and for example, a known thermosetting or ultraviolet curing resist may be used. The method of placing the etching resist is also not particularly limited, and a method of placing a film-like resist film, a method of applying by screen printing or inkjet, etc. may be used. Furthermore, the unnecessary portion of the bonding layer 30 may be further removed from the metal / ceramic bonded body 100 from which the unnecessary portion of the metal member 10 has been removed by etching.

[0053] (3) Effects According to this embodiment, one or more of the following effects can be obtained.

[0054] (a) In this embodiment, an active metal compound phase 33 containing a compound of an active metal element is present in the first layer 31. The presence of the active metal compound phase 33 in the first layer 31 can mitigate the generation of thermal stress caused by the difference in thermal expansion coefficient between the metal member 10 and the ceramic member 20, thereby improving the bonding strength and thermal cycle reliability.

[0055] (b) In this embodiment, the active metal compound phase 33 is preferably present so as to surround at least one of the Ag phase 31A and the Cu phase 31B. The presence of the active metal compound phase 33 in such a manner can reduce the generation of thermal stress between the Ag phase 31A and the Cu phase 31B, and can further improve the bonding strength and the thermal cycle reliability.

[0056] (c) In this embodiment, it is preferable that at least one of a carbide of an active metal element, a nitride of an active metal element, and an oxide of an active metal element is present in the active metal compound phase 33. When the active metal compound phase 33 is present in such a manner, it becomes easier to alleviate the generation of thermal stress between the Ag phase 31A and the Cu phase 31B, and it is possible to further improve the bonding strength and the thermal cycle reliability. In particular, when multiple types of active metal compounds are present in the active metal compound phase 33, the effect of improving the thermal cycle reliability becomes remarkable.

[0057] (d) In this embodiment, it is possible to dramatically increase the bonding strength between the metal member 10 and the ceramic member 20. For example, it is possible to make the shear strength of the bonding layer 30 10 MPa or more, preferably 50 MPa or more. Also, it is possible to make the tensile strength of the bonding layer 30 17.3 MPa or more, preferably 86.6 MPa or more.

[0058] (e) In this embodiment, it is possible to dramatically improve the thermal cycle reliability of the metal / ceramic bonded body 100. For example, when a thermal cycle of −50° C. for 30 minutes and 150° C. for 30 minutes is performed for 200 cycles, no cracking of the ceramic member 20 and no peeling of the metal member 10 are observed, and high thermal cycle reliability can be realized.

[0059] <Other Aspects of the Disclosure> Although the embodiments of the present disclosure have been specifically described above, the present disclosure is not limited to the above embodiments and can be modified in various ways without departing from the spirit and scope of the present disclosure.

[0060] The metal / ceramic bonded body 100 in this embodiment is not limited to use as an insulating circuit board, but can be widely used in a variety of applications, such as heat sinks and components of internal combustion engines and power generating machines. Even in these cases, the same effects as those of the above embodiment can be obtained. EXAMPLES

[0061] (Preparation of samples 1 to 7) As the ceramic members, a Si3N4 substrate of 50mm x 50mm x 0.32mm and an AlN substrate of 50mm x 50mm x 0.635mm were prepared. As the metal members, a Cu plate of 48mm x 48mm x 0.8mm was prepared for the Si3N4 substrate, and a Cu plate of 48mm x 48mm x 0.3mm was prepared for the AlN substrate. As the brazing material, Ag, Cu, and Ti powders were mixed in a predetermined ratio to form a paste. Ag and Cu powders with an average particle size of 45μm or less were used. In forming the paste, polyethylene glycol and diethylene glycol monobutyl ether with a molecular weight of 400 or less were used as solvents, and the ratio of the solvent in the paste was 10 mass%. The element mixing ratio (weight ratio) of Ag:Cu:Ti in the paste was 73:25:2. This paste was applied to the intended joining surface of the ceramic members by screen printing, and a metal member was placed directly on the applied paste film to obtain a laminate. The obtained laminate was pressurized with a force of 1 to 8 kPa in the lamination direction, and then placed in a heating furnace, where a carbon content adjustment process was performed so that the carbon content in the brazing material was 0.1 mass% to 10 mass%. Samples 1 and 2 were then heat-treated for 60 minutes at a bonding temperature of 850°C in an N2 atmosphere (containing 3% H2), samples 3 and 4 were heat-treated for 60 minutes at a bonding temperature of 820°C in a vacuum atmosphere, and samples 5 and 6 were heat-treated for 60 minutes at a bonding temperature of 820°C in an Ar atmosphere (containing 3% H2), to produce samples 1 to 6.

[0062] For sample 7, an Al2O3 substrate measuring 50 mm x 50 mm x 0.635 mm was prepared as the ceramic member. A Cu plate measuring 48 mm x 48 mm x 0.3 mm was prepared as the metal member. Ag and Cu powders with an average particle size of about 100 μm were used as the raw material for the brazing material. A degreasing process was performed before bonding, so that the carbon content in the brazing material was less than 0.1 mass%. The bonding temperature was 780°C, and the atmosphere was vacuum. Other conditions were the same as those for sample 1.

[0063] (Presence or absence of active metal compound phase) The presence or absence of an active metal compound phase in the first layer was determined by observing and analyzing the cross section of the bonded body using a scanning electron microscope (SEM) and a scanning transmission electron microscope (STEM). A random piece of about 10 mm x 10 mm was cut out from the obtained metal / ceramic bonded body, embedded in resin, and the cross section of the bonded body was polished to obtain a sample for SEM observation. A sample for STEM observation was processed by focused ion beam (FIB) so that it included a region in the first layer where an active metal compound phase was thought to exist. Using STEM, a range of 5 μm x 5 μm was observed at an acceleration voltage of 200 kV and a magnification of 400,000 times, and the spectrum was analyzed using electron energy loss spectroscopy (EELS). As shown in FIG. 4, if two peaks were observed in the range of 450 to 470 eV, it was determined that an active metal compound phase had been formed, and this is indicated by "◯" in Table 1. If the peaks were not observed, it was determined that an active metal compound phase had not been formed, and this is indicated by "×" in Table 1.

[0064] (Bonding strength test) A shear strength test of the bonding layer was performed on the obtained metal / ceramic bonded bodies (samples 1 to 7). In this test, first, for the obtained samples 1 to 7, the metal member was processed into a cylindrical shape with a diameter of 3 mm and a height of 2 mm, and the bonding surface of the surrounding ceramic member was exposed to prepare a test piece. Then, as shown in FIG. 7, with the ceramic member of the test piece fixed, the cylindrical metal member was pressed using a displacement jig along a direction parallel to the bonding surface, and the magnitude of the stress when the bonding layer broke (shear fracture) was measured, and the shear strength of the bonding layer was calculated based on the value. The shear test position (contact height H of the displacement jig) was set at a height of 200 μm from the exposed surface of the ceramic member, and the movement speed of the displacement axis was set to 100 μm / s. If the shear strength was 50 MPa or more, it was indicated with an "O" in Table 1, if the shear strength was 10 MPa or more and less than 50 MPa, it was indicated with a "△" in Table 1, and if the shear strength was less than 10 MPa, it was indicated with an "X" in Table 1.

[0065] (Reliability test) A thermal cycle test was carried out on the obtained metal / ceramic bonded bodies (samples 1 to 7). The test conditions consisted of 200 thermal cycles of -50°C for 30 minutes and 150°C for 30 minutes. Every 50 cycles, the presence or absence of cracks in the ceramic members and peeling of the metal members was judged by ultrasonic flaw detection (SAT) inspection. When no cracks in the ceramic members and peeling of the metal members were observed, this is indicated by "◯" in Table 1, when partial cracks in the ceramic members or partial peeling of the metal members were observed, this is indicated by "△" in Table 1, and when large cracks in the ceramic members or large peeling of the metal members were observed, this is indicated by "X" in Table 1.

[0066] [Table 1]

[0067] As shown in Table 1, Samples 1 to 6, in which an active metal compound phase was formed in the first layer, had high bonding strength, and no cracking of the ceramic member or peeling of the metal member was observed when a thermal cycle test was performed. On the other hand, Sample 7, in which an active metal compound phase was not formed in the first layer, had a slightly lower bonding strength, and cracking of the ceramic member or peeling of the metal member was observed when a thermal cycle test was performed. From the above, it was confirmed that by forming an active metal compound phase in the first layer, a metal / ceramic bonded body having high bonding strength and high thermal cycle reliability can be obtained.

[0068] <Preferred aspects of the present disclosure> Preferred aspects of the present disclosure will be described below.

[0069] According to one aspect of the present disclosure, A metal member; a ceramic member joined to the metal member; a bonding layer formed on a bonding surface between the metal member and the ceramic member, the bonding layer containing Ag and Cu and further containing at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er; The bonding layer is A first layer that forms an interface with the metal member and includes an Ag phase mainly composed of Ag and a Cu phase mainly composed of Cu; a second layer that forms an interface with the ceramic member, contains a compound of the active metal element, and is in contact with the first layer; A metal / ceramic joint is provided in which an active metal compound phase containing a compound of the active metal element is present in the first layer.

[0070] Preferably, The active metal compound phase exists so as to surround at least one of the Ag phase and the Cu phase.

[0071] Preferably, The active metal compound phase contains at least one of a carbide of the active metal element, a nitride of the active metal element, and an oxide of the active metal element.

[0072] Preferably, In a cross section of the first layer, the area ratio of the active metal compound phase is 15% or less.

[0073] Preferably, The cross section of the first layer is 500 μm 2 When the area ratio of the active metal compound phase in the region is measured multiple times in different observation fields, the difference between the maximum value and the minimum value of the area ratio of the active metal compound phase is 10% or more.

[0074] Preferably, The bonding layer contains 50 to 80 at % Ag, 10 to 40 at % Cu, and a total of 0.1 to 10 at % of the active metal elements.

[0075] Preferably, When the test piece was subjected to 200 cycles of a thermal cycle of -50°C for 30 minutes and 150°C for 30 minutes, no cracking of the ceramic member and no peeling of the metal member were observed.

[0076] According to another aspect of the present disclosure, A step of arranging a metal member and a ceramic member so as to be laminated with a brazing material interposed therebetween; and heating and holding the laminate of the metal member and the ceramic member while applying pressure in a lamination direction, The brazing material contains 50 to 80 at % Ag, 10 to 40 at % Cu, and a total of 0.1 to 10 at % of at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er, and the Ag and Cu are contained in a state where the average particle size is 45 μm or less. The method for producing a metal / ceramic bonded body includes a step of holding at a predetermined first temperature and a step of holding at a temperature higher than the first temperature, and at the end of the step of holding at the first temperature, the carbon content in the brazing material is 0.1 mass% or more and 10 mass% or less. [Explanation of symbols]

[0077] 100 Metal / ceramic joint 100' Laminate 10 Metallic parts 10s joint surface 20 Ceramic materials 20s joint surface 30 Bonding layer 31 1st layer 31A Ag phase 31B Cu phase 32 2nd layer 33 Active metal compound phase 50 Brazing material

Claims

1. A metal member; a ceramic member joined to the metal member; a bonding layer formed on a bonding surface between the metal member and the ceramic member, the bonding layer including Ag and Cu, and further including at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er; The bonding layer is a first layer that forms an interface with the metal member and includes an Ag phase mainly composed of Ag and a Cu phase mainly composed of Cu; a second layer that forms an interface with the ceramic member, contains a compound of the active metal element, and is in contact with the first layer; A metal / ceramic bonded article, wherein the first layer contains an active metal compound phase containing a compound of the active metal element.

2. 2. The metal / ceramic bonded body according to claim 1, wherein the active metal compound phase is present so as to surround at least one of the Ag phase and the Cu phase.

3. 2. The metal / ceramic bonded body according to claim 1, wherein the active metal compound phase contains at least one of a carbide of the active metal element, a nitride of the active metal element, and an oxide of the active metal element.

4. 2. The metal / ceramic bonded body according to claim 1, wherein an area ratio of the active metal compound phase in a cross section of the first layer is 15% or less.

5. The cross section of the first layer is 500 μm 2 2. The metal / ceramic joined body according to claim 1, wherein, when an area ratio of the active metal compound phase in the region is measured multiple times in different observation fields, a difference between a maximum value and a minimum value of the area ratio of the active metal compound phase is 10% or more.

6. 2. The metal / ceramic bonded body according to claim 1, wherein the bonding layer contains 50 to 80 at % Ag, 10 to 40 at % Cu, and a total of 0.1 to 10 at % of the active metal elements.

7. 2. The metal / ceramic bonded body according to claim 1, wherein when subjected to 200 cycles of thermal cycles of −50° C. for 30 minutes and 150° C. for 30 minutes, no cracking of the ceramic member and no peeling of the metal member are observed.

8. A step of arranging a metal member and a ceramic member so as to be laminated with a brazing material interposed therebetween; and heating and holding the laminate of the metal member and the ceramic member while applying pressure in a lamination direction, The brazing material contains 50 to 80 at % Ag, 10 to 40 at % Cu, and a total of 0.1 to 10 at % of at least one active metal element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mg, Ca, Y, Ce, La, Sm, Yb, Nd, Gd, and Er, and the Ag and Cu are contained in a state where the average particle size is 45 μm or less. the heating and holding step includes a step of holding at a predetermined first temperature and a step of holding at a temperature higher than the first temperature, and at a completion point of the step of holding at the first temperature, a carbon content in the brazing material is 0.1 mass% or more and 10 mass% or less.

Citation Information

Patent Citations

  • Map information creation device, map information creation method, program, and recording medium

    JP6743073B2

  • Copper / ceramic assembly, insulated circuit board, method for producing copper / ceramic assembly, and method for producing insulated circuit board

    WO2021033421A1